2017
DOI: 10.1007/s00125-017-4412-2
|View full text |Cite
|
Sign up to set email alerts
|

KLF10 transcription factor regulates hepatic glucose metabolism in mice

Abstract: KLF10 is an important regulator of hepatic glucose metabolism and modulation of KLF10 expression in the liver may be an attractive approach for the treatment of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Notably, KLF10 is the most up‐regulated gene in the 86 selected genes and its association with kidney disease is not yet known. KLF10 was originally identified as a TGF‐β‐inducible early gene 1 (TIEG) in human osteoblasts and often functions as a transcriptional repressor involved in multiple cellular processes (Subramaniam et al , , ; McConnell & Yang, ; Yang et al , ). We therefore decided to further investigate the role of KLF10 in podocyte injury.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, KLF10 is the most up‐regulated gene in the 86 selected genes and its association with kidney disease is not yet known. KLF10 was originally identified as a TGF‐β‐inducible early gene 1 (TIEG) in human osteoblasts and often functions as a transcriptional repressor involved in multiple cellular processes (Subramaniam et al , , ; McConnell & Yang, ; Yang et al , ). We therefore decided to further investigate the role of KLF10 in podocyte injury.…”
Section: Resultsmentioning
confidence: 99%
“…KLF10 could be added to the growing list of KLF family members which function in the regulation of adipogenesis. The role of KLF10 in metabolism had been defined in the liver (39,40). But it is still unknown whether KLF10 also plays a role in the metabolism of other tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In C57BL/6 mice, the mRNA and protein expression level of KLF10 was significantly increased in diet-induced non-alcoholic steatohepatitis and collagen producing activated hepatic stellate cells (21). Klf10 expression was upregulated in the livers of diabetic and obese ob/ob mice and that knockdown of Klf10 significantly inhibited the hepatic expression of gluconeogenic genes, decreased blood glucose levels and improved glucose tolerance (19). Our study showed that EMP treatment could obviously reduce the expression level of Klf10 (Figures 4C, 6D).…”
Section: Discussionmentioning
confidence: 98%
“…GO analysis revealed that EMP treatment significantly downregulated genes in the metal ion binding pathway ( Figure 4B), which involved in various biological functions, include lipid and glucose metabolism (such as Klf10, Atp2a2, and Enpp2), mitochondrial function (such as Ndufs1, Oma1, and Pde12) and β-cell function (such as Atp2a2 and Vav2), et al Our study showed that EMP treatment could significantly improve glucose tolerance and dyslipidemia, and alleviate insulin resistance in T2D rats ( Table 2 and Figure 1C), which may be associated with the effect of EMP on the expression of related genes in the metal ion binding pathway. KLF10 is a member of the Krüppel-like family of transcription factors (Klfs), which has been shown to be implicated in many biological processes, including cell differentiation, apoptosis and glucose metabolism (17)(18)(19)(20). In C57BL/6 mice, the mRNA and protein expression level of KLF10 was significantly increased in diet-induced non-alcoholic steatohepatitis and collagen producing activated hepatic stellate cells (21).…”
Section: Discussionmentioning
confidence: 99%